A study of the effectiveness to use electronic educational resources with web analytics tools (on the example of a departmental University of the Ministry of Emergency Situations of Russia) - V. V. Bulgakov (Открытое образование (Москва))
Purpose of research. The purpose of this work is to study the effectiveness of the use of electronic educational resources and their demand for students. The availability of digital technologies and readiness of students and lecturers to study in the electronic educational environment ensure the active development of this form of educational process organization. To assess the effectiveness and demand for electronic educational resources, data on the parameters of operation and user interaction with educational material are required.Materials and methods. To obtain data on the operating parameters and users’ work in the electronic educational environment, it is proposed to use a multi-level automated system for training, monitoring and analysis of theoretical knowledge – the Fire Test program, which is designed to organize and implement training in higher education programs of the specialty 20.05.01 – Fire Protection, 40.05.03 – Forensic Examination, the direction of training 20.03.01 – Technosphere Safety and the educational program of secondary vocational education 20.02.04 – Fire Protection. The Fire Test program is available on the Internet and allows you to conduct independent testing on specialties, disciplines, subjects of disciplines, as well as to carry out self-monitoring and knowledge control by lecturers online. As a tool for evaluating the effectiveness and relevance of the Fire Test program, it is proposed to use the web analytics service – Yandex.Metrica. To monitor the Fire Test program, we have selected key parameters that characterize the number of users and their activity in the electronic educational environment, which include demographic parameters, parameters of activity and loyalty of trainees, and technology parameters.Results. Based on the results of monitoring demographic parameters, which included the age of the audience during the study period of 1 month, the Fire Test program received an average of 27 visits from lecturers and 15 visits from trainees. Visitors from the number of students were 87%, from the number of Faculty Members – 13%. Monitoring user activity by time spent in the Fire Test program showed that students spent an average of 8 minutes 57 seconds on the site, and lecturers – 10 minutes 32 seconds. The largest number of visits of trainees was made during classes from 8-00 to 14-00 (55%), during the period outside of training sessions and self-training from 17-00 to 22-00 (23%), there was a uniform appeal of trainees to the Fire Test program. According to the monitoring of the loyalty parameter, during the study period, 12% of users accessed the site only 1 time, the largest number of users (48%) worked in the Fire Test program from 16 to 127 times, and more than 128 times 13% of users accessed the site. Monitoring of the technology parameter showed that smartphones are used as the main device for working in the Fire Test program, the share of which is 88.2%. The main operating systems used on smartphones are iOS (51%) and Google Android (37%), while the most popular browsers are Mobile Safari (44%).Conclusion. The results of the study allow us to conclude about the effectiveness and relevance of the electronic educational environment implemented by the Fire Test program among the trainees of Ivanovo Fire and Rescue Academy of the State Fire Service of the Ministry of Emergency Situations of Russia, as evidenced by their loyalty and activity in remote operation with the educational material.